2011
DOI: 10.1002/ijc.25936
|View full text |Cite
|
Sign up to set email alerts
|

Implication of human nonmetastatic clone 23 Type 1 and its downstream gene lipocalin 2 in metastasis and patient's survival of cancer of uterine cervix

Abstract: Human nonmetastatic clone 23 Type 1 (nm23-H1) is demonstrated to have diverse roles in metastasis and survival for many cancers, which are probably caused via different impacts on its downstream genes. Our preliminary study using cDNA genechip found that lipocalin 2 seems to be a significant downstream gene of nm23-H1 in SiHa cancer cells of uterine cervix. Therefore, we investigated the expression and correlation of nm23-H1 and lipocalin 2 in cancer metastasis and their implication in recurrence and survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…LCN2 has also been demonstrated to inhibit invasion and angiogenesis in pancreatic cancer [ 33 ]. In a study by Wang and colleagues [ 34 ], knockdown of nm23-H1 in SiHa uterine cervical cancer cells was shown to increase LCN2 promoter activity and gene expression, thereby decreasing cell migration and invasion. These authors' investigation of the correlation between LCN2 and nm23-H1 expression in cancer metastasis suggested that the LCN2 gene is an important downstream target of nm23-H1 in SiHa cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 has also been demonstrated to inhibit invasion and angiogenesis in pancreatic cancer [ 33 ]. In a study by Wang and colleagues [ 34 ], knockdown of nm23-H1 in SiHa uterine cervical cancer cells was shown to increase LCN2 promoter activity and gene expression, thereby decreasing cell migration and invasion. These authors' investigation of the correlation between LCN2 and nm23-H1 expression in cancer metastasis suggested that the LCN2 gene is an important downstream target of nm23-H1 in SiHa cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarray sections (MaxArray with 96 tissue cores in each tissue microarray, Zymed Laboratories Inc.) were incubated with anti-RRM2 antibodies (ab57653, Abcam Inc. MA, USA). A semi-quantitative H score of RRM2 immunoreactivity was determined by multiplying the proportional score of stained cells by their immunoreactivity intensity [14], [15]. The primary clinical endpoint was to correlate the expression of RRM2 with the survival of patients with cervical cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of NGAL in carcinogenesis is dependent on cancer type. Upregulation of NGAL increases cell infiltration in breast, bladder, stomach, gynecological, thyroid, lung, esophageal, colon and chronic myeloid leukemia; but in pancreatic and oral cancer, it reduces cell infiltration (18,19). In addition, upregulation of NGAL can increase the proliferation of cervical cancer and lung cancer cells (20,21).…”
Section: Introductionmentioning
confidence: 99%